INVESTMENT ANALYSIS OF A 5 MW GEOTHERMAL BINARY CYCLE POWER PLANT - Suardi Nur; Mulyadi Abdul Wahid (Indonesian Journal of Environmental Sustainability, 2023)
Indonesia is blessed with around 27.510 MWe of geothermal resources. Amongst the numbers, some resources are identified as small-scale geothermal resources. The development of small-scale geothermal resources is quite challenging either to government or private developers due to their low selling price that varies from USD 6.50 cent/kWh to USD 9.76 cent/kWh depending on the location and capacity. The challenges can be multiplied in the case of the electricity produced from a geothermal power plant that located isolated grid, where the electricity is unable to be transmitted to another load areas. Therefore, the electricity production will be limited to only serve the demand in the island that consequently will limit the revenue from electricity sales. This study analyzes the financial aspect of a binary geothermal power plant with gross installed capacity of 5 MW located in isolated island. The analysis shows the power plant will be financially feasible when the electricity selling price is over USD 30 cent/kWh that will generate 12% of IRR which is assumed as feasible target for this project. Furthermore, if environmental benefit is included the project can be feasible at lower selling price of USD 25 cent/kWh.